The impact of multi-layer corporate governance on banks' performance under the GFC and the COVID-19: A cross-country panel analysis approach - Oumniya Amrani; Amal Najab (Journal of Risk and Financial Management, 2023)
This paper examines the impact of multi-layer corporate governance (MCG) on banks' performance under the global financial crisis (GFC) and COVID-19. Using a random and fixed effects method, we regressed the impact of MCG variables on return on assets (ROA), return on equity (ROE), and non-performing loans (NPL) of a panel data of 44 conventional banks (CBs) and 40 Islamic banks (IBs), across 17 countries, and over the period from 2006 to 2020. The results show that board of directors (BoD)' structure has no association with CBs performance whereas the chief executive officer (CEO) duality is strongly negatively impacting CBs performance, especially during the GFC. In addition, supervision framework proxies have a strong positive influence on CBs performance, especially in the period after the GFC. Furthermore, cross-membership and the size of the Shariah board (SB) have a significant negative influence on IBs' performance, but SB qualification has a positive non-significant impact overall-with the exception of NPLs, which had a positive significant impact during the GFC. The supervision position has a favorable impact on IBs performance except during crises.
Keywords: 650; COVID-19; GFC; banks' performance; multi-layer corporate governance; panel data regression